143k views
2 votes
Complete the square. leave your anwser in the form (_)^2=_. x^2-6x=5​

Complete the square. leave your anwser in the form (_)^2=_. x^2-6x=5​-example-1
User Sabir
by
5.3k points

1 Answer

6 votes

Answer:

(x − 3)² = 14

Explanation:

To complete the square:

1) If the leading coefficient (coefficient of x²) is not 1, divide both sides by the leading coefficient.

2) Take the x coefficient, divide it by 2, square the result, and add to both sides.

3) Factor the perfect square.

x² − 6x = 5

Here, the leading coefficient is already 1.

The square of half of -6 is: (-6/2)² = (-3)² = 9. Add 9 to both sides.

x² − 6x + 9 = 5 + 9

x² − 6x + 9 = 14

Factor.

(x − 3)² = 14

User Hassan Siddiqui
by
6.6k points